QUANTITATIVE EVALUATION OF THE MITRAL VALVE BY MULTI-SLICE COMPUTED TOMOGRAPHY FOR PLANNING MINIMAL INVASIVE OR PERCUTANEOUS INTERVENTIONS - Musayeva, L.B.; Solovyova, N.V.; Syundermann, S.H. (World of Medicine and Biology, 2024)
24 healthy patients vs22 patients with functional mitral regurgitation (grade II/III) who had undergone ECG-gated computed tomography angiography were retrospectively evaluated. Mean age was 47±11 vs 63±7 years (p